Antifungal activity of lactic acid bacteria against pathogenic Sclerotium rolfsi of Capsicum annum plant - Zakaria, Siti Fatimah; Lani, Mohd Nizam; Chuah, Tse Seng; Ahmad, Fisal; Ahmad, Khairulmazmi (2016)
Sclerotium rolfsii is one of the most destructive soil-borne pathogen of chili plant (Capsicum annum) causing damping-off seedlings, stem rot, root rot, southern blight, and wilt. Those diseases can reduce quality and quantity of produce resulting in economic loss. Lactic Acid Bacteria (LAB) are known to have antifungal activity were used as bio-control agent against S. rolfsii. The aim of this study was to determine the antifungal activity of LAB that responsible towards inhibiting the S. rolfsii causing root and stem rot of chili plant. Identification of LAB from different fermentation products (corn kernel silage and fermented catfish) were done by phenotypic identification (API 50 CHL) and molecular technique (16S rDNA sequencing). Cell free supernatant (CFS) of 23 LAB strains (Lactobacillus plantarum, and Pediococcus pentosaceus) were tested for antifungal activity on Potato Dextrose Agar (PDA). Results showed that 15 of the strains LAB from fermented catfish showed greater inhibitory activity (52.9% to 71.4%) against S. rolfsii after incubation at 28ºC for three days compared with the control treatment (S. rolfsii growth in PDA without CFS of LAB). Further study will be focusing on the role of partially purified bacteriocin of LAB in reducing contamination of this pathogen.